ADJECTIVE AND IT’S TYPES IN TWO DIFFERENT LANGUAGES. - Avelbekova Nursila; Bafoyeva Nilufar Salimovna (PEDAGOGS, 2024)
Annotation: This article explores the similarities and differences in the usage of adjectives between English and Uzbek languages. It outlines the basic functions of adjectives and their various types in both languages, including descriptive, demonstrative, possessive, quantitative, and interrogative adjectives. While highlighting differences in adjective formation and structure, such as possessive adjectives and comparative/superlative forms, the article emphasizes the shared fundamental roles of adjectives in modifying nouns. Understanding these similarities and differences can aid learners in effectively navigating the nuances of adjectival usage in both languages.